INSETOS ASSOCIADOS Ã€ CULTURA DA ALFACE EM CAMPO LARGO, PARANÃ, BRASIL - Santos, Benedito Baptista dos; Cosmo, Paulo Carlos; Polack, Simone Weber (REVISTA DE AGRICULTURA, 2015)
INSETOS ASSOCIADOS Ã€ CULTURA DA ALFACE EM CAMPO LARGO, PARANÃ, BRASIL